Aptamers 2017 at Oxford. (2018) - Henri, Justin; McKeague, Maureen; Johnson, Philip E; Suess, Beatrix; Nakamura, Yoshikazu; Nilsen-Hamilton, Marit; Pastor, Fernando; Hahn, Ulrich; Bunka, David; Shigdar, Sarah
No abstract available